Pendugaan Heritabilitas dan Korelasi Genetik Berat Umur 21 Hari dan Berat Umur 35 Hari pada Mencit - Cahyowati, Meireni; Febrianta, Harvey; Ufidiyati, Nain; Maharani, Nadia; Wicaksono, Yananto Aryo (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to determine the genetic potential of mice by estimating their weight at 21 days old and 35 days old. Mice are one of the rodents used in education for learning purposes, such as practical work, research, and experimental animals, as well as in the food, pharmaceutical, and cosmetics industries. The importance of mice in education and industry has led to efforts to maintain their quality through genetic improvement. This study utilized data from 258 mice, including 20 male mice and 43 female mice. Heritability estimates and genetic correlation estimates were calculated using the half-sib correlation method. The estimated heritability value for 21-day-old weight in mice was 0.72 ± 0.27, and the estimated heritability value for 35 days old weight in mice was 0.88 ± 0.30. The estimated heritability values for 21 days old weight and 35 days old weight in mice fall into the category of high heritability. The estimated genetic correlation between 21 days old weight and 35 days old weight in mice was 0.34 ± 0.22, which falls into the category of positive and moderate genetic correlation. Based on the results of the heritability and genetic correlation estimates for 21 days old weight and 35 days old weight, mice show good genetic potential.